2019
DOI: 10.5897/ijmms2018.1386
|View full text |Cite
|
Sign up to set email alerts
|

Common ultramarathon trail running injuries and illnesses: A review (2007-2016)

Abstract: Regardless of the significant growth of ultra-marathon trail-running races over the last 40 years, epidemiological research is lacking. Presently, no review paper exists that integrates the empirical surveillances of ultra-marathon trail runners' injuries and illnesses. The purpose of this work is to integrate the empirical findings of injuries and illness among trail runners during the period 2007-2016. An electronic database search was conducted using Pubmed, Medline, Science Direct, Ebscohost, Biomed, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…An example of this is the study conducted by Matos et al (2019) on trail running, which found no significant changes in the load between the four weeks studied, thus suggesting a possible lack of variation across the weeks and not following principles of progression or variability of the load aimed at promoting adaptations [14]. In addition, for trail running and in the epidemiology of injuries, several studies [45][46][47] demonstrated that the most frequent regions of injury occurrence are the lower back, hip joint, knee, ankle, and foot, while the most common injuries are of the musculoskeletal typology, such as Achilles tendinopathy, iliotibial band syndrome, femoral patellar syndrome, stress fractures, and plantar fasciitis, suggesting that overuse is the leading cause of injuries. This emphasized the importance of training periodization to avoid injuries and overtraining.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is the study conducted by Matos et al (2019) on trail running, which found no significant changes in the load between the four weeks studied, thus suggesting a possible lack of variation across the weeks and not following principles of progression or variability of the load aimed at promoting adaptations [14]. In addition, for trail running and in the epidemiology of injuries, several studies [45][46][47] demonstrated that the most frequent regions of injury occurrence are the lower back, hip joint, knee, ankle, and foot, while the most common injuries are of the musculoskeletal typology, such as Achilles tendinopathy, iliotibial band syndrome, femoral patellar syndrome, stress fractures, and plantar fasciitis, suggesting that overuse is the leading cause of injuries. This emphasized the importance of training periodization to avoid injuries and overtraining.…”
Section: Introductionmentioning
confidence: 99%
“…Subungual hematomas, which appear as a collection of blood below the nail plate, are one of the most common types of dermatologic injuries that can bedevil runners after a race 13 , 14 . These injuries can lead to significant subjective-perceived discomfort due to the pressure forces that develop at the nail bed and may cause temporary limitations of activities.…”
Section: Introductionmentioning
confidence: 99%
“…These injuries can lead to significant subjective-perceived discomfort due to the pressure forces that develop at the nail bed and may cause temporary limitations of activities. In some cases they could further result in long-term complications such as secondary fungal infections and nail plate deformities 13,14 . It has been widely documented that the repetitive contact between the nail bed and toebox of the shoe is responsible for developing subungual hematomas and numerous factors such as poor shoe fit, steep terrain, and lower extremity edema play important roles in this process 9,[12][13][14] .…”
mentioning
confidence: 99%
See 1 more Smart Citation